2015
DOI: 10.1017/s0007114515004900
|View full text |Cite
|
Sign up to set email alerts
|

Dietary iron concentration influences serum concentrations of manganese in rats consuming organic or inorganic sources of manganese

Abstract: To determine the effects of dietary Fe concentration on Mn bioavailability in rats fed inorganic or organic Mn sources, fifty-four 22-d-old male rats were randomly assigned and fed a basal diet (2·63 mg Fe/kg) supplemented with 0 (low Fe (L-Fe)), 35 (adequate Fe (A-Fe)) or 175 (high Fe (H-Fe)) mg Fe/kg with 10 mg Mn/kg from MnSO 4 or Mn-lysine chelate (MnLys). Tissues were harvested after 21 d of feeding. Serum Mn was greater (P < 0·05) in MnLys rats than in MnSO 4 rats, and in L-Fe rats than in A-Fe or H-Fe r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Providing Fe-dextran via this route for 2-day-old calves resulted in improved RBC parameters, increase of Fe in blood and weight gain during the first month of life in neonatal dairy calves [ 1 ]. High iron content in the diet of other species like rats resulted in decreased growth [ 28 ]. In our own studies, the amount of Fe contained in PIC did not significantly affect the rate of body weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…Providing Fe-dextran via this route for 2-day-old calves resulted in improved RBC parameters, increase of Fe in blood and weight gain during the first month of life in neonatal dairy calves [ 1 ]. High iron content in the diet of other species like rats resulted in decreased growth [ 28 ]. In our own studies, the amount of Fe contained in PIC did not significantly affect the rate of body weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…The RNA isolation and real‐time PCR were performed as previously described (Zhang et al., ). Briefly, total RNA was extracted from snap‐frozen liver using Trizol reagent (Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The RNA isolation and real-time PCR were performed as previously described (Zhang et al, 2016 Table 2. Gene-specific amplification was determined by melting curve analysis and agarose gel electrophoresis.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
“…Hepcidin is released in response to increased iron status and binds to the cellular iron efflux protein, ferroportin (i.e., MTP1), causing ferroportin to be degraded, thereby reducing dietary iron absorption. Other investigators have shown marked increases in HAMP mRNA expression in the liver of rats fed a diet high in iron (Zhang et al, 2016). Decreases in hepcidin gene expression have also been observed in Mn-exposed welders (Fan et al, 2016).…”
Section: Discussionmentioning
confidence: 91%